Medisinsk profesjonalitet: Mestring av legeyrket - Stensland, Per; Nessa, John; Schei, Edvin (Nordisk tidsskrift for helseforskning, 2014)
When the doctor uses theoretical knowledge, clinical skills, and clinical communication in a way that takes care of the patient, this may be called professionalism. The article aims to show that medical professionalism, in all specialities, may be understood and taught through the two complex concepts “leadership” and “patient-centred medicine”.The article is built on a literature-search with a selection of articles based on the authors’ experience in the field.Leadership is an implicit part of clinical work. The concept gives a perspective on the solution of clinical problems and gives a frame for understanding interaction in consultations and in other professional relations. The doctor personal leadership actualizes professional tutoring as part of the education.Models for patient-centred medicine have emphasized the doctor’s attitudes, skills, and use of linguistic means, and they have deepened the doctor’s understanding for exploring the patient’s problem. Newer models also discuss the doctor’s actions and therapeutic actions and underscorethe leader-role in series of decision-making moments in the consultation. Patient-centred clinical work should be based on an understanding of the doctor as an active co-editor and co-producer of the patient’s illness narrative.Professionalism, interpreted as patient-centred leadership, gives a direction for medical education that may help doctors to cope with their work.
Keywords: Professionalism; leadership; patient-centred medicine; narrative medicine; shared decision-making; Profesjonalitet; lederskap; pasientsentrert medisin; narrativ medisin; pasientmedvirkning